1990
DOI: 10.1177/105381519001400104
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Preparation of Special Educators to Serve Infants with Handicaps and Their Families: Current Status and Training Needs

Abstract: The rapid increase in services for infants with handicaps and their famiies has heightened the need for qualified special education professionals. This article reports the results of a telephone survey to a random sample of preservice training programs, a mail survey sent to programs with an infancy or early childhood focus, and a working conference with leaders in infant personnel preparation. The purpose of those activities was to determine the current status of preparing special educators to work with infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…With a program philosophy in place, the committee defined the roles of an early educator in an integrated setting. This task involved examination of roles supported in the literature (Bailey, Palsha, & Huntington, 1990;McCollum, 1987) and delineation of the primary roles for which this program would prepare personnel. The next step was to establish the knowledge and skills required to fulfill those roles by reviewing recommended personnel guidelines from early childhood and early childhood special education organizations (ATE, 1990;McCollum et al, 1989;NAEYC, 1988).…”
Section: Process For Program Developmentmentioning
confidence: 99%
“…With a program philosophy in place, the committee defined the roles of an early educator in an integrated setting. This task involved examination of roles supported in the literature (Bailey, Palsha, & Huntington, 1990;McCollum, 1987) and delineation of the primary roles for which this program would prepare personnel. The next step was to establish the knowledge and skills required to fulfill those roles by reviewing recommended personnel guidelines from early childhood and early childhood special education organizations (ATE, 1990;McCollum et al, 1989;NAEYC, 1988).…”
Section: Process For Program Developmentmentioning
confidence: 99%
“…However, the lower faculty ratings given for importance to Knowledge of Team Work and Communication Skills could explain the gap often reported between recommended and current practices in early intervention programs. Despite the appeal and dedication to involving families as equal team members and decision-makers, professionals who reportedly provide families with few meaningful choices and only limited roles in decisions regarding their child's and family's IFSP (McBride, et al, 1993) may in fact be students of programs that failed to provide adequate content/practice related to needed communication skills with parents and professionals from other disciplines (Bailey, Palsha & Huntington, 1990;Rousch et al, 1992). Students may require multiple exposures over time or different instructional approaches to adequately learn the more applied content associated with the topics of Team Work and Communication Skills.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the survey results, the authors concluded that institutions of higher education are not producing the number of fully qualified personnel needed to meet the needs of the early intervention labor force. Several other authors have suggested that institutions of higher education are not adequately preparing early education and intervention personnel to implement family-centered services (Bailey, Palsha & Huntington, 1990;Hanson & Lovett, 1992;Rousch, Harrison, Palsha & Davidson, 1992;Winton, 1996). Based upon a review of the literature regarding professional roles and responsibilities in early childhood special education, Buysse and Wesley (1993) suggested that personnel preparation programs need to change in order to equip professionals with the consultation and teambuilding skills necessary to work effectively with families and other professionals.…”
mentioning
confidence: 99%
“…This group defi ned the core intervention competencies and responsibilities assigned to each discipline providing services under the IDEA through work groups of leaders representing each discipline (Bailey, Palsha, & Huntington, 1990 ) The ECSE group identifi ed the following to describe their mission: To ensure that environments for infants and toddlers (with disabilities) facilitate children's development in social, motor, communication, self-help cognitive, and behavioral skills and enhance children's self-concept, sense of competence, and control on independence. They also identifi ed 12 ECSE competencies that became the foundation of the CEC EC personnel specialty standards which continue to guide ECI pedagogy today.…”
Section: Fig 162 Relationship Between Program Development Criteria mentioning
confidence: 99%